Adolescent mental health utilization, virtual care, and community support: evidence from 2019 to 2022 - Zhou, William Youkang; Franzini, Luisa; Bustamante, Arturo Vargas (Frontiers in Public Health, 2025)
ObjectiveThis study examined racial and ethnic disparities in mental health service use, social support, and telemedicine access among U.S. adolescents between 2019 and 2022.MethodsWe analyzed nationally representative data from 2019 to 2022 National Health Interview Survey (NHIS) Sample Child Interview, focusing on adolescents aged 12–17. Multivariate logistic regression models with survey weights were used to assess disparities in outcomes by race and ethnicity.ResultsFrom 2019 to 2022, despite rising mental health needs, Black, Hispanic, and Asian adolescents were significantly less likely than White peers to take prescription medications (7–12 percentage points lower, p < 0.001), receive therapy (4–12 percentage points lower, p < 0.001), or receive both treatments (4–7 percentage points lower, p < 0.001). Hispanic and Asian adolescents were also 9 and 15 percentage points less likely (p < 0.001), respectively, to report receiving community support, while Black and Asian adolescents were 8 and 6 percentage points less likely (p < 0.001), respectively, to have had a virtual healthcare appointment.ConclusionsAccess to mental health services, virtual care, and community support remains disproportionately limited for racial and ethnic minority adolescents, even as overall mental health needs have worsened across all groups during the COVID-19 pandemic. The underuse of virtual care and community support among Hispanic and Asian adolescents underscores the urgent need for culturally responsive strategies to promote accessible and personalized mental health care for all adolescents.